MAGIA E MILAGRE: Duelos mágicos no Cristianismo Primitivo - ALMEIDA, ROBSON LUIZ DOMINGUES DE (2017)
This written work aims to addres the theme of Magic in the Mediterranean World at the period of Early Christianity. The Magic, wich, by its supernatural caracther, arouses interest and show the ways of relationship between human and sacred, at the same time that reveals several tensions and comprehensions about the popular religion´s practice. So, we construe the relationship between Magic and Miracle as so as the relationship of Magic and Religion. For this, we approach texts of Magic duels at canonical narratives, like Acts Of The Apostles 8. 4-25, that show common elements with the imagination of Early Christianity wich increase the tensions beteween Magicians and Apostles and enrich the presence and importance of the themeof Magic in the Mediterranean culture at the first centuries of the Christian Era. Especially in the face of this rivarly between thaumaturges, we can see the danger that Magic represented to the nascent Christianity and its identity in formation and the stratchs that the Magic bring for the teaching of the Apostles. So, after to broach the Magic elements at different narratives, we turn our attention to the Acts of Apostles, looking for the understanding of the importance of Luke´s narrative for the community of Early Christianity, especially in relation to the stricking and historical figure of Simon, The Magician. Simon was identified, historically, like the prototype heretic, Gnosticism´s father and Christianity´s corrupter, having borrowed his identity to represent all the way of corruptions of the apostolic teatching and ethical and moral deviations in the course of ecclesiastical history